The Application of Differential Pulse Polarography to the Analysis of Capecitabine and Investigation of Its Electroreduction Mechanism - ÇELİK, MELEK ŞİRİN (ELECTROCHEMICAL SOC INC, 2015)
The investigation of electrochemical reduction of capecitabine on DME resulted in a reduction scheme that involves a two electron reduction of the C=O bond on the six membered heterocyclic ring and comparison with model compounds such as benzophenone, 5-fluorouracil and cytosine supported the observed behavior. Reporting an inexpensive, simple, rapid and validated method for determination of capecitabine was achieved by DPP with good precision, accuracy and reproducibility. This work emphasizes polarography to be the best method of choice when studying reduction mechanisms and presents an example of its use for electroanalytical purposes. (C) 2015 The Electrochemical Society. All rights reserved.
Keywords: MASS-SPECTROMETRY; METABOLITES; PHARMACOKINETICS; FLUOROPYRIMIDINE; 5-FLUOROURACIL; DRUG